Study of Drug Utilisation and Adverse Drug Reaction Pattern of Anti-glaucoma Drugs in Patients with Primary Open Angle Glaucoma Attending the Glaucoma Clinic at a Tertiary Care Institute in Bihar, India: A Cross-sectional Study - Nitu Pandey; Sachin Kumar; Vidya Bhushan Kumar; Rinky Thakur (Journal of Clinical and Diagnostic Research)
Primary Open Angle Glaucoma (POAG) is a leading cause of secondary blindness, with pharmacotherapy being the mainstay of treatment. As guidelines and recommendations have evolved, so have prescribing trends. The present study was carried out to assess the utilisation pattern and Adverse Drug Reactions (ADRs) of anti-glaucoma drugs in POAG patients to promote their rational and cost-effective use. Aim: To evaluate the drug utilisation pattern and ADRs associated with anti-glaucoma drugs in POAG patients. Materials and Methods: This observational cross-sectional study was conducted at the Department of Pharmacology and the Regional Institute of Ophthalmology (RIO) at IGIMS, Patna, Bihar, India, for a period of six months (December 2023 to May 2024) and included 87 outpatients over 18 years of age diagnosed with POAG. Their prescriptions were analysed for the number and types of drugs, Fixed Dose Combinations (FDCs) and costs {the costs were obtained from Drug Today (April-July 2024); for drugs not available in this source, the online platform (Tata 1 mg) was used). The ADR pattern was observed in 78 participants who were already on anti-glaucoma drugs through inquiry and examination; nine were newly diagnosed and thus their ADRs could not be evaluated. Descriptive statistics were used. Results: Of the 87 participants, 48 (55.17%) were males and the remaining were females, with a mean age of 53.75±14.83 years. Of the 147 drugs and FDCs prescribed, 145 (98.64%) were topical (eye drops). A single drug was prescribed in 24 (27.59%) instances, while a single FDC was prescribed in 10 (11.5%) of the prescriptions. A total of 50 FDCs were prescribed, with an average of 2.3 drugs per prescription. Prostaglandin (PG) analogues were the most frequently prescribed drugs, followed by beta-blockers (timolol), accounting for 60 (31.09%) and 51 (26.42%) prescriptions, respectively. Carbonic anhydrase inhibitors accounted for 49 (25.39%), α-adrenergic agonists for 29 (15.03%) and Rho-kinase inhibitors for 4 (2.07%) prescriptions. All medications were prescribed as branded generics with complete dosing information regarding dose, dosage form and dose frequency. Out of 78 patients, 23 experienced ADRs, the most common being dryness, burning and grittiness; timolol was the most commonly implicated drug. No significant systemic ADRs were observed except for frequent urination with oral acetazolamide. All data were entered into Microsoft Excel and statistically analysed. Conclusion: The present study highlights the current prescribing practices in POAG, with a shift from beta-blockers to PG analogues reflecting current guidelines. The increased use of FDCs offers cost-effectiveness and convenience. The choice of branded generics over generic drugs remains a topic for further investigation.